Climate‐driven build‐up of temporal isolation within a recently formed avian hybrid zone. (1st February 2018) - Sirkiä, Päivi M.; McFarlane, S. Eryn; Jones, William; Wheatcroft, David; Ålund, Murielle; Rybinski, Jakub; Qvarnström, Anna
Abstract: Divergence in the onset of reproduction can act as an important source of reproductive isolation (i.e., allochronic isolation ) between co‐occurring young species, but evidence for the evolutionary processes leading to such divergence is often indirect. While advancing spring seasons strongly affect the onset of reproduction in many taxa, it remains largely unexplored whether contemporary spring advancement directly affects allochronic isolation between young species. We examined how increasing spring temperatures affected onset of reproduction and thereby hybridization between pied and collared flycatchers ( Ficedula spp.) across habitat types in a young secondary contact zone. We found that both species have advanced their timing of breeding in 14 years. However, selection on pied flycatchers to breed earlier was weaker, resulting in a slower response to advancing springs compared to collared flycatchers and thereby build‐up of allochronic isolation between the species. We argue that a preadaptation to a broader niche use (diet) of pied flycatchers explains the slower response to raising spring temperature, but that reduced risk to hybridize may contribute to further divergence in the onset of breeding in the future. Our results show that minor differences in the response to environmental change of co‐occurring closely related species can quickly cause allochronic isolation.